The efficacy and safety of roxadustat for anemia in patients with dialysis-dependent chronic kidney disease: a systematic review and meta-analysis - Qiaoqiao Zhou; Mian Mao; Jing Li; Furong Deng (Renal Failure, 2023)
Background This meta-analysis aims to assess the efficacy and safety of roxadustat in treating anemia patients with dialysis-dependent (DD) chronic kidney disease (CKD).Methods We comprehensively searched 5 databases for randomized controlled trials (RCTs) investigating roxadustat for anemia in DD-CKD patients. RevMan 5.0 was used to extract and synthesize data for meta-analysis.Results Ten different RCTs (9 studies) and 5698 DD-CKD patients with anemia were included. Our findings revealed that when compared to the erythropoiesis-stimulating agents (ESAs) group, the roxadustat group showed increased hemoglobin levels [MD (Mean Difference) 0.25 g/dL (95%CI 0.14 g/dL to 0.36 g/dL), p < 0.00001] and improved iron-utilization by increasing serum iron [MD 1.85 µmol/L], total iron binding capacity [MD 35.73 µg/dL], transferrin saturation [MD 1.19%], and transferrin level [MD 0.40 g/L]. In addition, we found that roxadustat significantly decreased the low-density lipoprotein-cholesterol [MD −0.39 mmol/L] and total cholesterol [MD −0.6 mmol/L]. In patients with a C-reactive protein level that exceeds the upper limit of the normal range, hemoglobin levels were higher for roxadustat than for ESAs [MD 0.39 g/dL]. Treatment-emergent adverse events, treatment-emergent serious adverse events, and major adverse cardiovascular events were not significantly different between the two groups.Conclusions The hemoglobin levels of DD-CKD patients were significantly increased and not affected by the inflammatory state after roxadustat treatment. Roxadustat also improved iron utilization, and it was not associated with higher treatment-emergent adverse events, treatment-emergent serious adverse events, and major adverse cardiovascular events when compared to ESAs.